In Vivo Activity of Posaconazole against Mucor spp. in an Immunosuppressed-Mouse Model - Sun, Qiu N. (American Society for Microbiology, 2002)
The in vivo activities of posaconazole, itraconazole, and amphotericin B in neutropenic mice with zygomycosis were compared. The in vitro MICs of posaconazole and itraconazole for the strains of Mucor spp. used in this study ranged from 0.125 to 8 μg/ml and 0.25 to 8 μg/ml, respectively. The in vitro MIC range for amphotericin B is 0.125 to 0.25 μg/ml. At twice-daily doses of ≥15 mg/kg of body weight, posaconazole prolonged the survival of the mice and reduced tissue burden.